Edukasi Ilmu Nahwu â€œJurumiyahâ€ Tingkat Pemula di PP. Al-Maâ€™ruf Jurang Wuluh Kedawung Mojo Kediri - Nur Hasanah; Muhammad Al Faruq (LP3M IAIFA Kediri, 2021)
In learning must always use the learning model because the learning model is needed and also as a learning tool in order to achieve the learning goals. The learning model can be interpreted as an approach used by learning activities to achieve desired learning outcomes. In this study focused on the book of Al-Jurumiyah.This research is qualitative research, a type of field research with a background in Madrasah Diniyah Pondok Pesantren Al-Ma'ruf. Aim to find out the model used in madrasah diniyah PP. Al-Ma'ruf in the study of the book of Al-Jurumiyah and know the factors of inhibition and support. Based on research, that the models used in the learning of the book of Jurumiyah in madrasah diniyah PP. Al-Ma'ruf is using the qiyasiyah and istiqroniyah methods as the mainstay method in the learning of the Book of Jurumiyah. In addition to using these methods, teachers use additional methods to maximize learning, provide assignments and conduct evaluations with the aim of knowing if students have understood the nahwu science material that has been given. While the obstacles faced by teachers and students are the allocation of limited learning time, diverse santri background, understanding of learning received by students is not the same, there are no additional extra extracurricular hours.